Effect of Cold Rolling Reduction and Testing Temperature to the Pitting Corrosion Resistance of UNS N06625 Based on ASTM G48 C - Diwang Ariyoseto, Huda
Corrosion is a phenomenon that happens naturally on metallic materials in order to achieve an electrochemical equilibrium. This phenomenon causes severe damage if it’s not well-controlled. The easiest corrosion control technique is by properly selection of material used. Nickel-base alloys is one of many options when a components is used of extreme conditions such as in a severe corrosive environment and high temperature, one of them is UNS N06625 or commercially known as inconel 625. This material can withstand various kind of corrosion attacks, especially pitting corrosion. This type of corrosion is very dangerous if it’s not well-understood due to its nature to cause a catastrophic disaster. In its fabrication processs, components generally will undergo forming process at first. However, this forming process that gives metals a plastic deformation could decrease corrosion resistance especially pitting corrosion resistance. This research is undertaken to determine the effect of cold working process through cold rolling on pitting corrosion resistance of UNS N06625. The testing is done based on ASTM G48 Method C to observe the critical pitting temperature (CPT) change. The testing is carried out on three different temperatures that are 78oC, 88oC and 95oC. Thickness reductions given by cold rolling process were 0%, 50%, 60% and 70%. The corrosive solution used on this experiment base onthe standard were ferric chloride (FeCl3.6H2O). immersion test in the corrosive solution was carried out with stirring speed at 250rpm for 72 hours. Experiment results shows the CPT for annealed sample is beyond 95oC far from the theoritical CPT (83,5oC). Sample with 60% reduction has CPT value of 88,5oC and CPT samples with reduction of 50% and 70% couldn’t be determined due to insufficient data for extrapolation. The cold rolling process affect the pitting corrosion resistance showed from increasing mass loss percentage along with increasing reduction percentage. The higher temperature promote corrosion rate based on increasing of mass loss along with rising temperature. ASTM G48 seems give a conservative theoritical CPT prediction on nickel-based alloy indicated by much higher experimental CPT to compare with theoritical CPT.